Effect of temperature and salinity stress on growth and lipid composition of Shewanella gelidimarina - Nichols, David S. (2000)
The maximum growth temperature, the optimal growth temperature, and the estimated normal physiological range for growth of Shewanella gelidimarina are functions of water activity (a(w)), which can be manipulated by changing the concentration of sodium chloride. The growth temperatures at the boundaries of the normal physiological range for growth were characterized by increased variability in fatty acid composition. Under hyper- and hypoosmotic stress conditions at an a(w) of 0.993 (1.0% [wt/vol] NaCl) and at an a(w) of 0.977 (4.0% [wt/vol] NaCl) the proportion of certain fatty acids (monounsaturated and branched-chain fatty acids) was highly regulated and was inversely related to the growth rate over the entire temperature range. The physical states of lipids extracted from samples grown at stressful a(w) values at the boundaries of the normal physiological range exhibited no abrupt gel-liquid phase transitions when the lipids were analyzed as liposomes. Lipid packing and adaptational fatty acid composition responses are clearly influenced by differences in the temperature-salinity regime, which are reflected in overall cell function characteristics, such as the growth rate and the normal physiological range for growth.